The Impact of Organizational Climate on Teacher Enthusiasm: A Two-Staged Structural Equation Modelling-Artificial Neural Network Approach - Punia Poonam; Bala Manju (De Gruyter, 2023)
The purpose of this article is to examine the influence of the school organizational climate on teacher enthusiasm. A sample of 600 teachers was drawn using a multi-stage random sampling method. The study variables were assessed using two main instruments: the organizational climate scale and teacher's enthusiasm scale. A two-staged structural equation modelling and artificial neural network approach was used for the analysis. The study has unveiled the importance of the school's organizational climate in determining the enthusiasm level of teachers. All the dimensions of organizational climate acted as significant predictors in the model. The study encourages periodic examination of the school climate and teachers' enthusiasm to take any decisions or initiatives necessary to address deficiencies in schools.